2021
DOI: 10.1088/2043-6262/ac389e
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis paniculata absorbed ZnO nanofibers as a potential antimicrobial agent for biomedical applications

Abstract: The present study focuses on developing antimicrobial nanofibers with superhydrophobicity and insect repellent properties for wound dressing and biomedical applications. For the first time, Andrographis paniculata leaf extract was prepared and incorporated into ZnO nanofibers (AP-ZnO). The antifungal and antibacterial activities of AP-ZnO were tested using the agar plate method. Amid the bacteria and fungus strain tested, the prepared sample exhibited a greater efficiency against Staphylococcus aureus and Tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…In 2021, Brindha et al demonstrated the ZnO nanofiber formation absorbed with Andrographis paniculata (AP-ZnO) to test its antimicrobial property. These AP-ZnO possessed larvicidal activity as well against Aedes aegypti [95]. Recent studies have also revealed that when ZnO NPs were capped with histidine, it possessed effective photoluminescence (PL emission) properties.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In 2021, Brindha et al demonstrated the ZnO nanofiber formation absorbed with Andrographis paniculata (AP-ZnO) to test its antimicrobial property. These AP-ZnO possessed larvicidal activity as well against Aedes aegypti [95]. Recent studies have also revealed that when ZnO NPs were capped with histidine, it possessed effective photoluminescence (PL emission) properties.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Several viruses have the potential to attack the central nervous system and adjacent tissues, even if this is somewhat unusual [ 114 , 115 , 116 , 117 ]. Herpes simplex, Epstein-Barr, varicella zoster, cytomegalovirus, and influenza viruses are a few examples of potential sources.…”
Section: Common Brain Diseasesmentioning
confidence: 99%
“…However, PLA and PBAT are not compatible, which could be addressed by introducing a compatibilizer or chain extender. The most widely used commercial chain extender is the Joncryl ADR family Polymers 2024, 16, 1039 2 of 18 of copolymers composed of styrene, glycidyl methacrylate, and butyl acrylate. The ADR chain extender is expected to enhance the properties of the blends in film blow molding and the elongation at break [11].…”
Section: Introductionmentioning
confidence: 99%
“…When filled with nanocrystal cellulose-silver nanohybrids (NCC-Ag), the PBAT/PLA/NCC-Ag composite blend also exhibits antibacterial properties which could be used as potential antibacterial packaging material [ 14 ]. ZnO-based nanocomposites of different morphologies (spherical, hexagonal, nanofibers, and core–shell) have been extensively reported in the literature for their enhanced photocatalytic (degradation of methylene blue dye) and antibacterial activity (against E. coli and S. aureus ) [ 15 , 16 , 17 ]. The tetra-needle-like or tetrapod ZnO (T-ZnO) whisker was discovered in the 1940s and the method of preparation of T-ZnO was first reported in 1990 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%